Evaluation of vascular endothelial growth factor level in tears and aqueous among patients with non-proliferative diabetic retinopathy - Shahrudin, Azima Ahmad (2022)
Introduction Diabetic retinopathy is a reversible cause of blindness with early detection and treatment. Vascular endothelial growth factor (VEGF) plays an essential role in the pathogenesis of blindness-related diseases, such as diabetic retinopathy (DR). VEGF is largely produced intraocularly such as in vitreous and aqueous. As tears sampling is less invasive, evaluating the VEGF level in tears may provide an association of the disease process with ocular surface fluid. Objectives This study aims to evaluate the VEGF level in tears and aqueous among diabetes mellitus (DM) patients with non-proliferative diabetic retinopathy (NPDR) and their correlation. Method A cross-sectional study was conducted in Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II from July 2019 until November 2021. Fifty-one diabetic patients with no diabetic retinopathy (DR), 45 patients with NPDR, and 54 non-DM patients were enrolled in this study. Type 2 DM patients and non-DM patients that were planned for cataract surgery and fulfilled the selection criteria were included in the study. Tears were collected using a Schirmer strip before the operation and aqueous were collected via cornea paracentesis during cataract surgery. The concentration of VEGF was determined using an ELISA kit test. Results The mean VEGF concentration in tears was 46.9 ± 18.7 pg/ml in DM patients with NPDR, 46.7 ± 23.3 pg/ml in patients with no DR, and 40.1 ± 20.6 pg/ml in non-DM. There was no significant difference in mean VEGF level in tears between the three groups before and after adjusting for covariates (p = 0.180 and p = 0.155 respectively). VEGF concentration in aqueous was 217.5  89.2 pg/ml in patients with NPDR, 174.3  75.1 pg/ml in DM patients with no DR group, and 140.7  41.9 pg/ml in the non-DM group. There was a significant difference in mean VEGF level in aqueous between the three groups before and after adjusting for age, duration of DM, level of HbA1c, hypertension, dyslipidemia, and status of smoking (p < 0.001 and p = 0.004, respectively). Post hoc analysis showed VEGF level in NPDR was significantly higher than in no DR (p = 0.012) and non-DM (p = 0.033). There was a significant weak correlation of VEGF levels between tears and aqueous among diabetic patients (r = 0.201, p = 0.049). Conclusions This study demonstrated that aqueous levels of VEGF were significantly higher in DM patients with NPDR than in no DR and non-DM. The level of tears VEGF has little or no relationship to the level of aqueous VEGF. These findings suggest that aqueous VEGF may reflect the DR status.